Caconomics in the academic environment: the vicious rationality of imitation - Мирослава Кругляк (Філософія освіти)
The article highlights one of the possible explanations for the culture of imitation and the tendency toward lowering standards in the academic environment. It deals with the concept of caconomics, which was elaborated by Italian researchers Diego Gambetta and Gloria Origgi. Based on rational choice theory, they elaborate a model of a situation when participants prefer low-quality standards while declaring high-quality ones. This model allows to identify the structural factors behind unscrupulous academic practices. It shows that dishonesty and imitation may be not so much the result of the bad intentions of individuals, but rather a distorted norm that relies on a certain rational calculation within the framework of a vicious system. The concept of kakonomics turns out to be interesting and fruitful when considering the failures of reforms in Ukrainian science and education. In particular, the manifestation of the kakonomics mechanisms is demonstrated with the survey of publications of Ukrainian PhD and doctoral students in foreign journals. The requirement to have publications in such journals is intended to increase international visibility of Ukrainian researcher`s works. However, it turned out that most of the PhD and doctoral students (who submitted their dissertations in 2018-2022) had publications in low-quality or predatory journals. These data can serve as empirical evidence of the failure of reforms carried out through directive requirements imposed in a bureaucratic manner. Data also show that efforts to increase standards without taking into account the extent to which the academic environment is able to meet that new demands will encourage imitation. As a result, such situation leads to the system of anti-meritocratic selection, and researchers who truly adhere to high standards are disadvantaged compared to imitators.